2013
DOI: 10.1016/j.cortex.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of working memory capacity in the control of recollection

Abstract: The links between control over recollection and working memory capacity (WMC) were investigated using event-related potentials (ERPs) and behavioural assays. Electrophysiological evidence for a relationship between greater control over recollection and higher scores on a measure of WMC was obtained. In addition, people with high WMC who first completed a task requiring cognitive control showed no electrophysiological evidence for control over recollection on a subsequent task. This outcome suggests a causal li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
24
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 42 publications
10
24
1
Order By: Relevance
“…Critically, one group of participants was given a taxing Stroop task to complete prior to the exclusion task, and this group showed a smaller difference in amplitudes between target and non-target LP effects. This extended the individual differences evidence, causally implicating WMC in the ability to control recollection proactively [30]. …”
Section: Introductionsupporting
confidence: 63%
“…Critically, one group of participants was given a taxing Stroop task to complete prior to the exclusion task, and this group showed a smaller difference in amplitudes between target and non-target LP effects. This extended the individual differences evidence, causally implicating WMC in the ability to control recollection proactively [30]. …”
Section: Introductionsupporting
confidence: 63%
“…Although it is not possible to exclude this possibility here, it is worth noting that a similar source memory paradigm using comparable classes of source information also reported quicker RTs for location than conceptual information when left/right responses did not correspond with the side of the screen (Bridger & Wilding, 2010). Insofar as RT differences might indicate that more resources are available in one class of retrieval block, either because the corresponding source information is easier or quicker to retrieve, or because response requirements are easier to implement, the current data nonetheless do not correspond with previous reports in which resource-availability has been proposed to account for changes in selective retrieval (Elward et al, 2013). Such an account would expect selective retrieval to be greater in the easier perceptual condition, but the current data instead indicate more selective retrieval for conceptual information.…”
Section: Discussioncontrasting
confidence: 98%
“…The first of these factors is working memory capacity (WMC), following work from Elward, Evans, andWilding (2013, 2010) who showed that individuals with higher WMC show more pronounced ERP correlates of selective retrieval in the exclusion task, even when the likelihood of retrieving a target did not vary between WMC groups. These data points can be reconciled with Herron and Rugg's (2003) findings if one notes that in both paradigms, selective retrieval was more pronounced under conditions in which more resources were available (either because of high WMC or because target retrieval was easier).…”
mentioning
confidence: 99%
“…In particular, these authors point to common activations in both kinds of tasks in the prefrontal cortex, which are described as being common control and monitoring mechanisms. Rather than straying too far into this promising avenue for further research, we confine our comments to how working memory mechanisms may be used in the exclusion task, and draw largely on the arguments proposed by Wilding and colleagues (Elward and Wilding, 2010;Elward et al, 2013). One observation is that intact recollection is not necessary at all, should sufficient capacity and reserve exist in a short-term store.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…One recent development is the finding that the control component of recollection (i.e. as measured in exclusion tasks) draws heavily upon working memory resources (Elward & Wilding, 2010;Elward, Evans, & Wilding, 2013). Our view is that working memory resources would be necessary to hold in mind information at test and reflect metacognitively, or strategically upon it.…”
Section: Introductionmentioning
confidence: 99%